Investigating the Quality Performance of Production of Some Selected Drinks using Hotelling T-Square and Control Chart (Global Journal of Management and Business Research, 2020)
Consumers make complaint about the state of home-made goods, in fact many claim that foreign goods are of high quality compared to home-made goods. We discovered that many of our indigenous industries are no more in existence and so this brought the desire to carry out this research work so as to find out whether products from our indigenous brewery industry fall within the lay-down acceptable standard that is devoid of the consumers' complaint. The significance of this study is to ascertain the quality of drinks produced by checking whether some components which make up the quality of these brands are in control and to detect error in the production process. The data for this research were collected on three major components produced [Star, Maltina And Goldberg] for four months in one of our indigenous company and the readings reported was taken twice per day and averaged.
Keywords: control charts; cumulative sum technique charts; hotellings t-square; fill height